Buku Ilustrasi “Acaraki Journey” Sebagai Upaya Revitalisasi Budaya Jamu - Jesslyn Juana Elizabeth Hiu (VisArt: Jurnal Seni Rupa dan Design, 2025)
Jamu, as part of Indonesia's cultural heritage, faces significant challenges in maintaining its existence amid modernization, especially among younger generations. The declining interest in jamu risks causing a generational disconnect and the gradual disappearance of traditional herbal practices that have been passed down through centuries. In response to this issue, this research focuses on the design of an illustrated book titled “Acaraki Journey: The World of Jamu and Acaraki” as an educational and visual medium to support the revitalization of jamu culture. The study adopts a qualitative method involving literature studies, field observations, and collaboration with Acaraki, a modern jamu café in Jakarta that actively promotes jamu through workshops and community engagement. The visual narrative in the book is developed to be engaging, informative, and culturally rich, targeting young readers as well as domestic and international visitors. The result indicates that illustrated media can effectively convey complex cultural messages in a simplified and appealing format. This project aims to preserve the traditional knowledge of jamu-making and also to reposition jamu as a contemporary health practice embedded within modern lifestyles. Ultimately, the book is expected to become a bridge that connects the past and the future through accessible cultural storytelling.